RUSSIAN SLANG AND COLLOQUIALISM: A GUIDE TO INFORMAL RUSSIAN - Sultanmuradova Farangiz Akramovna; Samandarova Shahrizoda Valiyevna; Rustamova Malika Hamidovna (European Science Publishing, 2024)
This article provides an overview of Russian slang and colloquial language, highlighting its origins, characteristics, and usage in modern Russian society. Russian slang has diverse roots, including criminal jargon, youth subcultures, and Western influences, and serves as an important tool for expressing emotions, attitudes, and cultural identity. The article explores popular slang words, technological and youth slang, as well as regional variations. Understanding Russian slang offers insights into contemporary Russian culture and enhances conversational fluency for language learners.
Keywords: Russian slang, Russian colloquial language, informal Russian,youth slang in Russian, Russian criminal jargon, regional slang variations, technology slang, Russian pop culture expressions, conversational Russian.